The Importance of Entrepreneurship Learning And Business Motivation Seminars To Increase The Desire To Be An Entrepreneur - Arifudin, Syamsul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Being an entrepreneur is very complicated, because there are many things that must be mastered, ranging from knowledge, expertise, marketing, management, to personal personality. So do not be surprised, people prefer to be employees. One way to become a business actor is to learn to do business, both theoretically and practically. In addition, to become a business actor, you must have a high self-confidence and enthusiasm, the way is by attending business motivation seminars or participating in entrepreneurial communities/forums. This study seeks to reveal the possibility of strengthening interest in entrepreneurship which is influenced by learning factors and attending entrepreneurship motivation seminars. To answer the research objectives, a scientific method was established, namely quantitative. The research subjects are startup business actors from among students in the Greater Jakarta area, who are currently building their businesses. The number of research samples was 150 people, which was obtained through distributing questionnaires on social media using the Google Forms application. The sampling technique uses simple randomization and data analysis uses regression statistics. The results showed that the desire for entrepreneurship was strengthened if knowledge and motivation about business increased, both in partial and simultaneous models. This explains that there is a positive trend, business actors are starting to find their way in business and enjoy being a businessman. Therefore, it is important for novice entrepreneurs to enrich themselves by learning a lot and getting business inspiration, which arouses the passion for entrepreneurship.